1985
DOI: 10.1111/j.1745-9125.1985.tb00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Sociological and Human Developmental Explanations of Crime: Conflict or Consensus?*

Abstract: This paper examines multidisciplinary correlates of delinquency in an attempt to integrate sociological and environmental theories of crime with human developmental and biological explanations of crime. Structural equation models are applied to assess links among biological. psychological, and environmental variables collected prospectively from birth through age 17 on a sample of 800 black children at high risk for learning and behavioral disorders. Results show that for both males and females, aggression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Research on crime and human nature has been fraught with disciplinary tensions, many of which stem from the unwarranted fear that “an emphasis upon the causative role of a biological–universal event [may serve] to downgrade the importance of other internal and contextual factors” (Cairns, personal communication, June 23, 1990; see also Denno, 1985; Wilson & Herrnstein, 1985). We trust that our study has allayed such fears, because, as we have shown, biological, dispositional, and contextual factors are all clearly implicated in the genesis of female delinquency.…”
Section: Discussionmentioning
confidence: 99%
“…Research on crime and human nature has been fraught with disciplinary tensions, many of which stem from the unwarranted fear that “an emphasis upon the causative role of a biological–universal event [may serve] to downgrade the importance of other internal and contextual factors” (Cairns, personal communication, June 23, 1990; see also Denno, 1985; Wilson & Herrnstein, 1985). We trust that our study has allayed such fears, because, as we have shown, biological, dispositional, and contextual factors are all clearly implicated in the genesis of female delinquency.…”
Section: Discussionmentioning
confidence: 99%
“…Gender is one of the strongest and most frequently documented predictors of delinquent and violent behavior (Denno, 1985;Rhodes & Fischer 1993;Rowe et al, 1995;Mears et al, 1998). Studies of overall crime rates have consistently shown higher rates of offending for males than for females (Rowe et al, 1995;Heidensohn, 1997), and especially higher rates of violence.…”
Section: Snfpr 15mentioning
confidence: 99%
“…25.)' l b o recent studies, however, found essentially no significant differences in handedness between offenders and nonoffenders (Denno, 1985;Hare & Forth, 1985; also see Hare & Connolly, 1987, p. 225). In a separate analysis of only the male portion of Denno's data, Nachshon and Denno (1987, p. 202) reported that there was actually a higher incidence of right-handedness among offenders than among nonoffenders.…”
Section: Higher Incidences Of Delinquency and Criminality Have Been Rmentioning
confidence: 88%
“…For example, only one of the studies (Denno, 1985) sampled female subjects, and only a few studies have considered aspects of sidedness other than handedness. Also, only official indicators (i.e., arrest, imprisonment) have been used thus far to measure delinquency and criminality.…”
Section: The Journal Of General Psychofogymentioning
confidence: 97%